A new species of Nazeris Fauvel, 1873 (Coleoptera, Staphylinidae, Paederinae) from Uttarakhand, Northern India - Shavrin, Alexey V. (Zootaxa, 2011)
Nazeris indicus Cameron, 1943, described from the Darjeeling Himalayan hill region of West Bengal (type locality: “Ghum district: Tiger Hill”) [Cameron, 1943:32], is currently the only species of the paederine genus Nazeris Fauvel, 1873 known from India. During a field trip to India in June 2011, I collected a new species of Nazeris from Uttarakhand province, which is described herein.